Pipeline to the Physician Assistant Profession: A Look to the Future. Issue 1 (March 2022) - VanderMeulen, Stephane; Snyder, Jennifer A.; Kohlhepp, William; Mustone Alexander, Lisa; Straker, Howard; Bowser, Jonathan; Bondy, Mary Jo
Abstract: The current pipeline of physician assistant (PA) school applicants reflects the future workforce of the profession, which is why the admissions process with all its components and variables is so important. Many studies have shown that a workforce that represents the patients it cares for leads to improved health outcomes, especially among underrepresented minority populations. Yet, PA programs have made little progress over the past 2 decades in increasing the diversity of matriculants and graduates. As a profession, it is our collective responsibility to intentionally advance diversity, equity, and inclusion, and examining the admissions process would be the most logical place to start.